Effect of Pistacia atlantica Mastic Extract on Experimental Wound Healing and Various Biochemical Parameters of Blood Serum in Rabbit Models - Sh Fakour; S Heydari; L Akradi; R Rahymi Bane (Institue of Medicinal Plants, ACECR, 2017)
Background: The mastic extract of Pistacia species can be considered as a natural herbal source in the pharmaceutical industry. Objective: The purpose of this study was to evaluate the effectiveness of Pistacia atlantica mastic on wound healing, oxidative and blood biochemical parameters. Methods: Topical cream and oral suspension was made of the mastic of P. atlantica, after preparing hydroalcoholic extract and essence. 40 male rabbits were selected (4 experimental groups and 4 control group). To induce oxidative stress and tissue damage the burn wound were created. Topical cream (1 gram 60% and 30%, 3 ml oral suspension 60% and 30%, respectively were used daily in treatment groups for 21 days. Inert cream and distilled water were used topically and orally in the control group, respectively. The oxidative parameters of blood serum including malondialdehyde (MDA), catalase, glutathione peroxidase, superoxide dismutase and biochemical parameters of low density and high lipoproteins, as well as glucose level were measured on day 1, 7, 14 and 21. The healing process and grading were evaluated by histological examination on day 21. Results: Increased concentration of MDA indicated the appearance of oxidative stress. oncentrations of SOD, CAT, GPX showed significant increases as compared with the control group and in day 1 (P≤0.05). The level of LDL did not show any difference in experimental group. Conclusion: The results show that mastic extract of P. atlantica has an appropriate effect on wound healing and can be used as a natural antioxidant.